IMPLEMENTASI GOOD UNIVERSITY GOVERNANCE TERHADAP KINERJA PERGURUAN TINGGI BADAN LAYANAN UMUM (STUDI KASUS UNIVERSITAS LAMPUNG) - Diannita Maharani (P3M STISIPOL Dharma Wacana Metro, 2022)
The University of Lampung is one of the state universities that carries out the mandate as a public service agency of education. In achieving its goal of producing professionals and capable of high competitiveness, the implementation of GUG must be applied to get better performance. This study aims to determine the implementation of GUG on performance at the University of Lampung. Data collection techniques were carried out through questionnaires. This type of research is a descriptive research with a quantitative method with a t-test. The results showed that there were significant differences in the implementation of GUG on performance between the head office and work units. This happens because the head office has more authority as a place for final decision making or as the centralization of all policies, while work units function as policy implementers with limited authority. At the head office, there are more adequate resources compared to work units, especially in terms of human resources, where employees who are considered qualified will be promoted to move to the head office, so that the work unit lacks reliable human resources